Soil Survey Relevant Information for Land Suitability Zoning and Territorial Planning. Case study Usumacinta Watershed Mexico - Lopez, Daniel M. Lopez; Guerrero, Aristides Saavedra (European Journal of Applied Sciences, 2023)
In Mexico during the last decades, the anthropic pressure exerted on natural ecosystems and land dedicated to productive activities has been increasing, causing intense negative environmental effects on soil, water, flora and fauna resources. These effects can be addressed through adequate land-use planning; an essential step for the definition and application of management programs is the zoning land by suitability. Soils, conceptualized as a natural body constitute a useful approach for the study and analysis of the natural system. Therefore, the objective of this article is to show the importance and the fundamental role of soil information, acquired through soil survey, in land suitability zoning and territorial planning. From database of soils, qualifiers of soil properties were used to define limitation related with effective soil depth, fertility, soil drainage and salinity - sodicity. Then for each one of these limitation factors, individual maps were constructed, which by a decision model were integrated in a final land suitability map. The results, according to this map show, in the lowlands where slope is less than 12%, three general groups of land suitability: Lands of classes I to III, with slight limitations to crop production(23.2%, of the total area), lands with moderate limitations class IV (8.2 %) y and lands of classes IV, V and VI with moderate to severe limitations,very poor drainage and flooding (24.4%). In the highlands, were the slope is higher than 12% have moderate (class IV, 10%) to severe limitations (VI-VII, 31%) and class VIII (3%).